Quality of life of mothers of children with Down syndrome: a study comparing those with and without hearing loss - Alkahtani, Rania; Bakry, Huny; Al Hawi, Lama M.; Alshehri, Jana D.; Elbeltagy, Reem (Frontiers in Psychiatry, 2025)
BackgroundDown syndrome is a genetic disorder present from birth, leading to various physical and cognitive challenges. Some children with Down syndrome also experience hearing loss. The combined impact of raising a child with Down syndrome and hearing loss can affect the quality of life (QoL) of mothers. The aim of this study was to examine the differences in QoL between mothers of children with Down syndrome who have hearing loss and those without hearing loss.MethodsA cross-sectional study was conducted with 103 mothers of children with Down syndrome. Data were collected using the Arabic version of the WHOQOL-BREF, which assesses the QoL across four domains, including physical health, psychological health, social relationships, and environment, with scores ranging from 0-100.ResultsIn the studied sample, 16.5% of mothers reported that their child had hearing loss. The mean QoL scores for the total sample were 65.8 ± 18.6 in physical health, 72.6 ± 17.5 in psychological health, 65.6 ± 13.7 in social relationships, and 68.7 ± 16.8 in environment. There were no significant differences in QoL scores across any domain between mothers of children with and without hearing loss (p > 0.05). Mothers’ perceptions of their overall QoL and health were high and similar between both groups.ConclusionMost mothers in this study reported satisfactory QoL. While HL does not seem to drastically affect overall QoL across various domains, it is evident that social challenges persist.